Application of Probiotics Based on Immunostimulant β-Glucan Saccharomyces cerevisiae Combination of Antibacterial Sonneratia alba Leaves as Vibrio harveyi Inhibitor of White Shrimp (Litopenaeus vannamei) - Alta Safina Azzahra; Siti Mufidah; Sadhya turahmi; Bryceton Bryant The; Ratih Novita Praja, drh., M. Si (Airlangga University, 2024)
Vibrio harveyi can cause mass death in vaname shrimp. The β-Glucan content in Saccharomyces cerevisiae can stimulate the immune system non- specifically. Meanwhile, the endophytic bacteria Sonneratia alba has antibacterial activity. This study aims to determine the effectiveness of the probiotic fee formulation of β Glucan S. cerevisiae using a combination of antibacterial S. alba leaves as an effort to inhibit the growth of V. harveyi in vaname shrimp (L. vannamei). The research method used is an experimental probiotic formulation from a combination of β Glucan S. cerevisiae and endophytic bacteria S. alba through shrimp feed with 6 treatments and 4 replications, The parameters used are Total Haemocyte Count, Differential Haemocyte Count and Survival Rate. This study was conducted in vivo tests for 10 days of probiotic feed maintenance and 7 days of infection with a total research period of four months at the Faculty of Health, Medicine, and Natural Sciences, Airlangga. The results of the research show that the combination of ingredients can inhibit the growth of V. harveyi through the immune response and survival of vannamei shrimp. The best treatment was P3 with a Total Haemocyte Count (THC) of 7,54x106 cells/ml and Differential Haemocyte Cout (DHC) (60,56% granular, 16,68% semi-granular, 22,76% hyaline) with 85% survival. The provision of probiotics had a real effect and became the optimum formulation to inhibit the growth of V. harveyi.